Poverty as a socio–economic problem in Russia - P. T. Ghukasyan (Путеводитель предпринимателя)
Poverty is a condition in which an individual or group has insufficient resources to meet their basic needs, such as food, water, shelter, clothing, medical care, and education. It can lead to a lack of access to the opportunities and resources necessary for a decent life, and limit opportunities for personal and professional development. In rural areas, the population has a predominantly underdeveloped transportation infrastructure. Working poverty is widespread in Russia — a condition when a person working on a permanent basis does not receive sufficient income to ensure a minimum standard of living. The article considers approaches to the definition of poverty, categories of the poor, legislative initiatives to support the poor population. Measures of targeted support to socially vulnerable categories of the population for further reduction of poverty in Russia are proposed.